The impact of inflation and gross domestic product on the banking index: the case of Turkey (Journal of Economic Research & Business Administration, 2025)
This study examines the effect of inflation and GDP on the banking index. As the research methodology, the stationarity of time series data was tested using the Augmented Dickey-Fuller (ADF) test, and analyzes were conducted using the Vector Auto regression (VAR) model and the Granger Causality Test. According to the findings, the banking index followed a general upward trend between 2005 and 2021, with a significant increase observed particularly after 2021. While the inflation rate remained low and stable from 2005 to 2019, it started to rise after 2019. GDP, on the other hand, consistently increased, indicating economic growth. Statistical analyzes revealed that inflation has a significant causal effect on the banking index, whereas GDP does not have a direct impact. Correlation tests showed that inflation has a positive relationship with both the banking index and GDP, and there is also a positive correlation between the banking index and GDP. This study highlights the significant effect of inflation on the banking index and emphasizes the necessity of considering this impact in economic policy decisions. Additionally, the lack of a direct effect of GDP on the banking index suggests that other macroeconomic factors and market dynamics play a more prominent role in the financial sector.Keywords: Inflation, GDP, Banking, Banking Index, BIST.